2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332702
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the effects of aligned collagen fibers and ascorbic acid derivatives on behavior of rabbit corneal fibroblasts

Abstract: The cornea is responsible for functional optical activity of the mammalian eye, as it must remain transparent in order to focus light onto the retina. Corneal disease is the second leading cause worldwide of vision loss [1]. Human donor tissue transplantation in the cornea is associated with problems such as immunorejection and recurring graft failures [1]. Tissue engineering offers a promising alternative to using human donor tissues in treating corneal diseases. A viable tissue-engineered cornea must be mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
1
1
1
Order By: Relevance
“…Consistent with previous studies, our pattern‐structured silk films provided a transparent appearance and not only supported cell attachment and proliferation, but also successfully guided the alignment of keratocytes and collagen fibrils in the direction of the grooves, which resembles the highly organized structure of the native cornea. However, in contrast to our results, previous studies have shown that the surface topography of materials may risk altering the gene expression of keratocyte markers and ECM synthesis . The discrepancies to our results in this regard may owe to the different materials used in the previous studies (collagen, polycaprolactone, etc.)…”
Section: Resultscontrasting
confidence: 99%
“…Consistent with previous studies, our pattern‐structured silk films provided a transparent appearance and not only supported cell attachment and proliferation, but also successfully guided the alignment of keratocytes and collagen fibrils in the direction of the grooves, which resembles the highly organized structure of the native cornea. However, in contrast to our results, previous studies have shown that the surface topography of materials may risk altering the gene expression of keratocyte markers and ECM synthesis . The discrepancies to our results in this regard may owe to the different materials used in the previous studies (collagen, polycaprolactone, etc.)…”
Section: Resultscontrasting
confidence: 99%
“…Because of that, ascorbic acid has been used to construct cell sheet for tissue engineering application . Ascorbic acid has also been introduced into the culture of corneal cells, mainly on the ECM production of keratocytes . It has been reported that human keratocytes cultured with ascorbic acid for 5 weeks could automatically assemble organized ECM with parallel arrays of fibrils, which are morphologically similar to the corneal stroma .…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, they should not trigger any inflammatory, adverse, or immunological responses that might result in scaffold rejection by the body [18]. So far, a large variety of biomaterials has been used to prepare ophthalmic scaffolds, including: natural proteins, such as collagens [4,60] and gelatin [61,62]; natural polysaccharides, such as alginate [63,64] and chitosan [65]; and synthetic polymers, such as poly lactic-co-glycolic acid (PLGA) [66,67] and poly(ε-caprolactone) (PCL) [48,68]. Each of these polymers has its own advantages and disadvantages [18].…”
Section: Scaffold Biocompatibilitymentioning
confidence: 99%